1999
DOI: 10.3133/ofr99310
|View full text |Cite
|
Sign up to set email alerts
|

Thickness of Cenozoic Deposits of Yucca Flat Inferred from Gravity Data, Nevada Test Site, Nevada

Abstract: The basin-basement contact for Yucca Flat was modeled using isostatic gravity data, a linear density-depth function for the basin deposits, and drill-hole constraints to produce a digital database of both the depth to basement and the gravitational anomaly associated with the basement rocks. The model predicts a depth of roughly 2,500 m in the deepest, southern part of the basin. The model shows offsets in the basement rocks along both the Carpetbag and Yucca faults. The basement rocks of Yucca Flat have a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(39 citation statements)
references
References 8 publications
2
37
0
Order By: Relevance
“…This inversion method is useful for predicting the relative shapes of basins, although determination of absolute basement depths is less certain because of uncertainties in the local density-depth relation for overlying sediments, and because basin-fi ll density is assumed to vary only in the vertical direction (Phelps et al, 1999). A larger issue in our case is the sparse basement exposures (critical constraints for the separation of the basement and basin-fi ll gravity fi elds) on the east side of the basin.…”
Section: -D Basin Geometrymentioning
confidence: 99%
“…This inversion method is useful for predicting the relative shapes of basins, although determination of absolute basement depths is less certain because of uncertainties in the local density-depth relation for overlying sediments, and because basin-fi ll density is assumed to vary only in the vertical direction (Phelps et al, 1999). A larger issue in our case is the sparse basement exposures (critical constraints for the separation of the basement and basin-fi ll gravity fi elds) on the east side of the basin.…”
Section: -D Basin Geometrymentioning
confidence: 99%
“…2). Phelps et al (1999) showed that lateral variations in basin-fi ll density, unless abrupt, do not change the overall modeled shape of the basin and that the method can be less effective in estimating the magnitude of basin thickness, especially in basins containing thick basalt fl ows or in areas of poor well control.…”
Section: Gravitymentioning
confidence: 99%
“…The method assumes no lateral density variations within the basin fill. This method is a useful tool for predicting the shapes of basins, but it can be less effective in estimating the actual magnitude of basin thicknesses because of uncertainties in the local density-depth relation and the assumption of one-dimensional variations (Phelps et al, 1999).…”
Section: Gravity Data and Basin Geometrymentioning
confidence: 99%